Acute Bacterial Suppurative Thyroiditis following Fine Needle Aspiration: A Case Report and Review of the Literature - Htet, Zaw Win (Case Rep Endocrinol, 2020)
BACKGROUND: Fine needle aspiration (FNA) of thyroid nodules is a simple, reliable, and inexpensive procedure performed on suspicious thyroid nodules found in thyroid ultrasound (US). Acute bacterial suppurative thyroiditis is an uncommon complication of FNA which, however, can be life threatening. Case Presentation. A 49-year-old lady presented with fever and neck pain 1 month after FNA with biochemical evidence of thyrotoxicosis. Repeat US of the thyroid showed interval enlargement of the thyroid nodule, and the culture of the cystic fluid of repeat FNA grew Propionibacterium acnes. She responded well to bedside aspiration and 2 weeks of antibiotic therapy without requiring surgical intervention. Discussion. Acute bacterial suppurative thyroiditis following FNA has been increasingly reported in immunocompetent hosts. There are 2 peculiar features in our case: a smoldering course caused by an indolent organism and a significant time lag between initial FNA and clinical presentation. On literature review, it was found that the onset of acute bacterial suppurative thyroiditis after FNA can range from a few days to up to 3 months. Clinicians should be aware of this complication even if FNA has been performed a few months ago. Thyroid US and US-guided FNA are useful initial investigations. Conventional management of acute bacterial suppurative thyroiditis has been surgery combined with antimicrobial therapy. However, recently, a more conservative approach has been reported to be effective in the treatment of acute bacterial suppurative thyroiditis as well. CONCLUSION: Proper infection control practices are necessary in performing the FNA. Initial management (conservative versus surgical) of acute bacterial thyroiditis should be based on the patient's clinical status and the extent of infective focus.